Leek Cultivation Guide for Florida - Mary Dixon; Guodong Liu (EDIS)
Leek (Allium porrum L.) is a member of Amaryllidaceae, a family with ornamental crops, like amaryllis, and with vegetable crops, like onion. Leek is a highly demanded vegetable because of its flavor and nutrient content. Although there is great potential for leek to be grown commercially in Florida due to demand and appropriate climatic conditions, the United States does not currently produce a significant quantity of leek compared to countries such as Indonesia, Turkey, and China. This new 7-page publication of the UF/IFAS Horticultural Sciences Department, written by Mary Dixon and Guodong Liu, provides a basic guide to cultivation of leek in Florida, as well as information on its agricultural, culinary, and medicinal uses. https://edis.ifas.ufl.edu/hs1388